Prospects for biodiesel production from Macrotermes nigeriensis: Process optimization and characterization of biodiesel properties. (March 2021) - Kalu-Uka, Godwin Mong; Kumar, Sandeep; Kalu-Uka, Abraham Chinedu; Vikram, Shruti; Okorafor, Okore Okay; Kigozi, Moses; Ihekweme, Gina Odochi; Onwualu, Azikiwe Peter
Abstract: The use of insects as feedstock for biodiesel production has sparsely been studied and very little is known of the fuel properties and engine performance of insect biodiesel. In this study, biodiesel was initially produced from an insect feedstock M. nigeriensis, then its physicochemical properties were characterized. The biodiesel was produced via the three-step process of lipid extraction, acid esterification (1 wt% H2 SO4 ) and alkaline transesterification (0.5 wt% NaOH). The optimal reaction time, temperature and methanol-oil molar ratio for the acid-esterification process resulted in a free fatty acid conversion of 96.58%. The volumetric yield, fatty acid methyl esters content and physicochemical properties of M. nigeriensis biodiesel were analyzed using various analytical equipment such as the GC-HRMS, and 1 H NMR. Analysis of the production process showed that 86.54 vol% biodiesel was obtained from M. nigeriensis oil. Further analysis showed that the biodiesel contained 96.72% fatty acid methyl esters. The composition of the fatty acid methyl esters was found to be 48% saturated esters and 52% monosaturated esters. The biodiesel density (841 kg m −3 ), viscosity (2.32 mm 2  s −1 ), flash point (125 °C), pour point (−15 °C), cetane number (51.4), higher heating value (41.8 MJ kg −1 ) and acid value (0.44 mgKOH.g −1 ) were in compliance with the ASTM D6751 standards. One of the important results to highlight is the remarkably low viscosity of the biodiesel, which is attributed to the high concentration of monounsaturated fatty acid methyl esters. Lower viscosity of fuel helps to improve fuel atomization and combustion efficiency, and hence lower emissions. The absence of polyunsaturated fatty acid esters also indicates that the biodiesel will have good oxidation stability. Graphical abstract: Image 1 Highlights: Analysis of the overall production process showed that M. nigeriensis biomass has 46.8% oil content, and 86.54 vol% of the oil content could be converted to biodiesel. An optimal FFA conversion of 96.58% was achieved by the acid esterification reaction, and the final biodiesel obtained by alkaline transesterification reaction had 96.72% FAME content. M. nigeriensis produced biodiesel with such a remarkably low viscosity (2.32 mm 2  s −1 ) that is needed to improve the fuel atomization and combustion efficiency of diesel engines. The absence of polyunsaturated fatty acid methyl esters in the FAME composition of the biodiesel is a good indication that the biodiesel will have an improved oxidation stability. All the properties of the biodiesel are in compliance with the ASTM D6751 standards.